ANALISIS HUKUM PIDANA TERHADAP PENCURIAN IKAN DI ZONA EKONOMI EKSKLUSIF INDONESIA WILAYAH PENGELOLAAN PERIKANAN REPUBLIK INDONESIA (STUDI PUTUSAN NO: 03/PID.SUS.P/2012/PN.MDN - Marudut Hutajulu; Alvi Syahrin; Mahmud Mulyadi; Marlina Marlina (USU LAW JOURNAL, 2014)
ABSTRACTIndonesia as an archipelago has an abundant of fish resources. Geographically, Indonesia is located strategically, for which this condition becomes a challenge, and it is our responsibility to maintain, guard, and conserve these resources. This strategic condition will automatically attract foreign ships to do illegal fishing, particularly in ZEEI (Indonesian Exclusive Economy Zone) in the Area of Fishery Management of the Republic of Indonesia. The result of the research showed that the consequence of the illegal fishing in the area of fishery management of the Republic of Indonesia by foreign fishermen is very big; it amounts to 30 quintillion rupihs each year. It is recommended that, in order to cope with the criminal act of illegal fishing in the Area of Fishery Management of the Republic of Indonesia, particularly in the Indonesia Exclusive Economi Zone, the government should be serious in enlarging the budget for the supervision and furnish equipment and infrastructure which are related to supervision.Keywords: Criminal Act of Illegal Fishing